Review of the Indo-West Pacific genus Inimicus (Synanceiidae: Choridactylinae) - Inaba, Tomoki; Motomura, Hiroyuki (Zootaxa, 2018)
The stinger genus Inimicus Jordan & Starks, 1904 (family Synanceiidae), distributed in the Indo-West Pacific, is characterized by having two free pectoral-fin rays. Examination of the original descriptions and 420 specimens, including all available type specimens, of the genus resulted in the recognition of nine valid species: Inimicus brachyrhynchus (Bleeker, 1874) (recorded from Hong Kong and Singapore), I. caledonicus (Sauvage, 1878) (distributed in Andaman Sea and western Pacific Ocean), I. cuvieri (Gray, 1835) (Andaman Sea and western Pacific Ocean), I. didactylus (Pallas, 1769) (western Pacific), I. filamentosus (Cuvier, 1829) (western Indian Ocean), I. gruzovi Mandrytsa, 1991 (Coral Sea), I. japonicus (Cuvier, 1829) (East Asia), I. sinensis (Valenciennes, 1833) (eastern Indian and western Pacific oceans), and I. smirnovi Mandrytsa, 1990 (southwestern Pacific Ocean). Inimicus joubini (Chevey, 1927), previously considered a valid species, is herein regarded as a junior synonym of I. japonicus. Another 10 nominal species are confirmed to be synonymized with the nine species. A revised diagnosis for each species and a key to all the species are provided.